ANALISIS DESKRIPTIF KUANTITATIF TERHADAP DISTRIBUSI DAN FAKTOR PENGHAMBAT PEMBERIAN IMUNISASI TETANUS TOXOID (TT) PADA IBU HAMIL - Baiq Ricca Afrida; Ni Putu Aryani; Susilia Idyawati; Sri Hawari Jannati; Raudatul Jannah (LPPM Universitas Abdurrab, 2025)
Neonatal tetanus is one of the leading causes of neonatal mortality due to Clostridium tetani infection, which commonly occurs as a result of non-sterile deliveries. Tetanus Toxoid (TT) immunization serves as the primary preventive measure by providing protection for pregnant women and their fetuses through antibody transfer. Although TT immunization has been recommended by the WHO and the government, its coverage remains low in certain regions. Therefore, this study aims to analyze the distribution of TT immunization among pregnant women and identify the factors contributing to the lack of immunization uptake. This study employs a descriptive quantitative method, collecting data through surveys conducted among 77 pregnant women in Lembar Selatan Village, Lembar District. The data were analyzed using frequency distribution and percentage calculations. The results indicate that 53% of pregnant women had not received TT immunization, with the primary reason being fear of side effects (85%). Additionally, a small proportion of respondents did not receive immunization due to insufficient gestational age (10%) and unavailability of the vaccine (5%). In conclusion, the low coverage of TT immunization in Lembar Selatan Village is influenced by concerns over side effects, despite a relatively high awareness of its benefits. Therefore, enhanced education and more intensive socialization efforts by healthcare workers, as well as improved access to immunization services for pregnant women, are necessary.